Impact assessment of 5G technology on economic sectors and proposal of a roadmap for 5G service deployment in Vietnam (Part 2) - Tuan, Tran Minh; Hung, Nguyen Phi; Hoa, Dang Thi; Bac, Nguyen Gia; Vu, Dong Hoang; Lan Anh, Dao Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
In the past, the fifth generation (5G) mobile network in Vietnam has been gradually deployed in tune with the world and it is ready for commercialization in the coming time. Therefore, actively researching, evaluating potential applications, and forecasting the impacts of 5G mobile technology on economic sectors will serve as a basis for proposing orientations for the development of potential 5G applications in Viet Nam. Making contributions to the policy makers and telecommunications providers to have a referenced landscape of 5G situation development in Vietnam before it is commercially deployed on a large scale. Due to the wide scope of the research, a part of its has been published in the Journal Science and Technology Policy and Management (No. 1+2/2021), which focuses on the following contents: (i) overview of 5G; (ii) the theoretical basis and methodology of the research to propose the 5G application development roadmap, which identifies the problem to be studied and solved; (iii) Potential applications of 5G from the user’s point of view; and (iv) Vietnam’s readiness for 5G deployment. To continue the research contents, in this article we continue to deliver the following contents: (i) forecast the impact of 5G on economic sectors of Vietnam; and (ii) propose a roadmap to deploy 5G applications; and (iii) some conclusions when the study completion. The article’s contents have partially shown the research results of the state-level project: "Research to propose a roadmap and policy for 5G deployment in Vietnam" Code: DTDLCN-10/20 Code: 21012501